Children Coping, Contextual Risk and Their Interplay During the COVID-19 Pandemic: A Spanish Case - Domínguez-Álvarez, Beatriz; López-Romero, Laura; Isdahl-Troye, Aimé; Gómez-Fraguela, Jose Antonio; Romero, Estrella (Frontiers in Psychology, 2020)
The COVID-19 pandemic has changed the lives of millions of people around the globe and some of the unprecedent emerged disruptions, are likely to have been particularly challenging for young children (e.g., school closures, social distancing measures, movement restrictions). Studying the impact of such extraordinary circumstances on their well-being is crucial to identify processes leading to risk and resilience. To better understand how Spanish children have adapted to the stressful disruptions resulting from the pandemic outbreak, we examined the effects of child coping and its interactions with contextual stressors (pandemic and family related) on child adjustment, incorporating in our analysis a developmental perspective. Data was collected in April 2020, through parent-reports, during the acute phase of the pandemic and, temporarily coinciding with the mandatory national quarantine period imposed by the Spanish Government. A sample of 1,123 Spanish children (50% girls) aged 3 to 12 (Mage = 7.26; SD = 2.39) participated in the study. Results showed differences in the use of specific strategies by children in different age groups (i.e., 3–6, 7–9 and 10–12-year-olds). Despite the uncontrollable nature of the pandemic-related stressors, child disengagement coping was distinctively associated to negative outcomes (i.e., higher levels of behavioral and emotional difficulties), whereas engagement coping predicted psychosocial adjustment across all age groups. Moreover, interactively with child coping, parent fear of the future and parent dispositional resilience appear as relevant contextual factors to predict both negative and positive outcomes, but their effects seem to be age dependent, suggesting a higher contextual vulnerability for younger children. These findings might have implications for identifying individual and contextual risk and informing potential preventive interventions aimed to reduce the impact of future pandemic outbreaks on children of different ages.